Penambahan Tepung Cangkang Udang dalam Pakan Buatan Sebagai Penguat Warna Ikan Koi (Cyprinus carpio L.) - Saloh, Arry Yusnita; Aida, Yuniarti; Zahida, Felicia (Universitas Atma Jaya Yogyakarta, 2005)
Shrimp’s skin and carapace has been used as color enhancement. The shrimp’s skinand carapace was pounded into flour and added to the commercial pellet availablelocally. The shrimp’s flours contains red pigmen astaxanthine. The Koi’s used in thisexperiment were two months old Cyprinus carpio L var kohaku. Five level of differentconcentration of shrimp’s flour were used i.e. 5.7%, 8.5%, 11.4%, 14.2%, and 17.1%respectively. Each aquarium contains three fishes were used in threeplicate and rearedfor 8 weeks. Five main color or hue was observed i.e. Redish Orange, Pastel Orange,Orange Red or Yellowish Red, Red and High Red or Vivid Red. 15 panelis have beenused to give their comments to the color enhancement. The results shows that the valueof the fish’s color didn’t change much, but the chrome intensity increase on week eight.Statistical analysis of Kruskall-Wallis and Mann-Whitney Test shows that on theconcentration of shrimp flour of 11,4% was giving the best value for hue and chrome.On the consentration of 14,2% and 17,1% the results were not strong enough. This isprobably because the concentration of the flour reaches maximum at 11,4% and givingmaksimum color enhancement level so that more additioing didn’t gave any change.